Basic research in HIV vaccinology is hampered by reductionist thinking - Van Regenmortel, Marc H. (Frontiers in Immunology, 2012)
This review describes the structure-based reverse vaccinology approach aimed at developing vaccine immunogens capable of inducing antibodies that broadly neutralize HIV-1. Some basic principles of protein immunochemistry are reviewed and the implications of the extensive polyspecificity of antibodies for vaccine development are underlined. Although it is natural for investigators to want to know the cause of an effective immunological intervention, the classic notion of causality is shown to have little explanatory value for a system as complex as the immune system, where any observed effect always results from many interactions between a large number of components. Causal explanations are reductive because a single factor is singled out for attention and given undue explanatory weight on its own. Other examples of the negative impact of reductionist thinking on HIV vaccine development are discussed. These include 1) the failure to distinguish between the chemical nature of antigenicity and the biological nature of immunogenicity, 2) the belief that when an HIV-1 epitope is reconstructed by rational design to better fit a neutralizing Mab, this will produce an immunogen able to elicit Abs with the same neutralizing capacity as the Ab used as template for designing the antigen 3) the belief that protection against infection can be analysed at the level of individual molecular interactions although it has meaning only at the level of an entire organism. The numerous unsuccessful strategies that have been used to design HIV-1 vaccine immunogens are described and it is suggested that the convergence of so many negative experimental results, justifies the conclusion that reverse vaccinology is unlikely to lead to the development of a preventive HIV-1 vaccine. Immune correlates of protection in vaccinees have not yet been identified because this will become feasible only retrospectively once an effective vaccine exists.